Endophytes: Colonization, Behaviour, and Their Role in Defense Mechanism - Anteneh Ademe Mengistu (International Journal of Microbiology)
Biotic and abiotic factors cause an enormous amount of yield and economical loss. However, endophytes can play a significant role in enhancing the tolerance of plants. Endophytes systematically colonize different parts of the host, but plants use a variety of defense mechanisms towards microbial infection. However, they have to survive the oxidative environments, and endophytes like Enterobacter sp. encode superoxide dismutases, catalases, and hydroperoxide reductases to cope up the oxidative stress during colonization. On the contrary, others produce subtilomycin which binds with flagella to affect flg22-induced plant defense. The behavior of endophytes can be affected by different genes in hydrolase activity when they come into contact with the host plant. The lifestyle of endophytes is influenced by environmental factors, the host, and microbial genotypes, as well as an imbalance in nutrient exchange between the microbe and the host. For instance, induction of PiAMT1 in root endophyte Piriformospora indica indicates depletion of nitrogen which plays as a triggering factor for activation of the saprotrophic program. Microbes enhance disease resistance through induced systemic resistance (ISR), and Bacillus cereus triggers ISR against Botrytis cinerea through an accumulation of the PR1 protein and activates MAPK signaling and WRKY53 gene expression by the JA/ET signaling pathway. Similarly, Trichoderma arundinaceum produces trichodiene that affects Botrytis cinerea through induction of defense-related genes encoding salicylic acid (SA) and jasmonate (JA). Overall, endophytes can play a vital role in disease management.